MEDIATION: An eMbEddeD system for auditory feedback of hand-water InterAcTION while swimming - Cesarini, D.; Calvaresi, D.; Farnesi, C.; Taddei, D.; Frediani, S.; Ungerechts, B. E.; Hermann, T. (Procedia Engineering, 2016)
In swimming sport, the proper perception of moving water masses is a key factor. This paper presents an embedded system for the acquisition of values of pressure on swimmers hands and their transformation into sound. The sound, obtained using sonification, is used as an auditive representation of hand-water interactions while swimming in water. The sound obtained is used as an auditive feedback for the swimmer and as an augmented communication channel between the swimming trainer and the athlete. The developed system is self-contained, battery powered and able to work continuously for over eight hours, thus, representing a viable solution for daily usage in swimmers training. Preliminary results from in-pool experiments with both novel and experienced swimmers demonstrate the high acceptability of this technology and its promising future evolution and usage possibilities.